2006
DOI: 10.1152/ajprenal.00068.2006
|View full text |Cite
|
Sign up to set email alerts
|

RS1 (RSC1A1) regulates the exocytotic pathway of Na+-d-glucose cotransporter SGLT1

Abstract: The product of gene RSC1A1, named RS1, participates in transcriptional and posttranscriptional regulation of the sodium-d-glucose cotransporter SGLT1. Using coexpression in oocytes of Xenopus laevis, posttranscriptional inhibition of human SGLT1 (hSGLT1) and some other transporters by human RS1 (hRS1) was demonstrated previously. In the present study, histidine-tagged hRS1 was expressed in oocytes or Sf9 cells and purified using nickel(II)-charged nitrilotriacetic acid-agarose. hRS1 protein was injected into o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
68
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 55 publications
6
68
0
Order By: Relevance
“…The observed changes in distribution correlated with functional data showing that RS1 down-regulates the transcrip-* This work was supported by Deutsche Forschungsgemeinschaft Grant SFB tion of SGLT1 in subconfluent LLC-PK 1 cells (25). In Xenopus oocytes, expression of SGLT1 was inhibited when human RS1 was coexpressed (23,24,27) or when purified RS1 protein was injected into SGLT1 expressing oocytes shortly before uptake measurements (21). This indicated that hSGLT1 was inhibited by hRS1 on the posttranscriptional level.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…The observed changes in distribution correlated with functional data showing that RS1 down-regulates the transcrip-* This work was supported by Deutsche Forschungsgemeinschaft Grant SFB tion of SGLT1 in subconfluent LLC-PK 1 cells (25). In Xenopus oocytes, expression of SGLT1 was inhibited when human RS1 was coexpressed (23,24,27) or when purified RS1 protein was injected into SGLT1 expressing oocytes shortly before uptake measurements (21). This indicated that hSGLT1 was inhibited by hRS1 on the posttranscriptional level.…”
supporting
confidence: 58%
“…Cyclic AMP, protein kinase A, protein kinase C (PKC), 3 and phosphoinositol 3-kinase are involved in the regulatory pathways (13,14,16). It has been shown that SGLT1 can be regulated by changes in transcription (12,17,18), mRNA stability (19), intracellular trafficking (14,16,20,21), and transporter activity (22). However, the individual regulatory pathways, their cross-talk, and their physiological importance are not understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, acute recovery of NMDAR current after MK-801 block may reflect mainly recycling NMDARs, whereas accumulation of surface NMDARs in YAC72 MSNs over the 6 h chlorpromazine treatment likely represents newly synthesized receptors mobilized from the Golgi. The latter process is not expected to be affected by chlorpromazine (Wang et al, 1993;Veyhl et al, 2006), yet new receptor insertion was not observed in wt MSNs and was only modest in YAC72 MSNs over a 6 h period. Chlorpromazine may have additional effects on receptor forward trafficking or else homeostatic changes in receptor exocytosis may be induced in response to blockade of endocytosis, as shown previously for AMPARs over a timescale of minutes (Lledo et al, 1998;Man et al, 2000;Wang and Linden, 2000) (for review, see Groc and Choquet, 2006).…”
Section: Altered Nmdar Trafficking In Mhtt-expressing Msnsmentioning
confidence: 98%
“…1,6 Because SGLT1 and SGLT2 are regulated by several kinases [7][8][9][10][11][12][13] and the protein RS1, 14,15 glucosuria could, at least in theory, also result from deranged function of those signaling molecules. Moreover, Na ϩ -coupled glucose transport is affected by dietary Na ϩ , 16 hyperglycemia, 16 intracellular Na ϩ activity, 17 transplantation, 18 and exposure to cadmium.…”
mentioning
confidence: 99%